The mechanism of drive system flexible suspension and its application in locomotives - Yao, Yuan; Zhang, Hong-Jun; Luo, Shi-Hui (Transport, 2015)
The drive system flexibly suspended on the bogie frame is conducive to the lateral dynamic performances of locomotive. In order to clarify the mechanism and optimize the suspension parameters using this model, a bogie dynamics model with 10 degrees of freedom (including the drive system) was established. The lateral dynamic performances were analyzed with the different suspension parameters. The mechanism was determined from the dynamic vibration absorber and the best suspension frequency of the drive system was put forward. The multi-body-dynamics model with two types of drive systems was simulated in locomotives to verify this theoretical analysis. When the suspension frequency is close to the hunting motion frequency of the wheelset, the locomotive dynamics performed the best. The length of the swing rods at the front and rear drive systems were different on the same bogie, which improved the locomotive dynamic performances within a wider range of speed and the wheel conicity. The track shift forces of the locomotive were reduced by 45% and 34% respectively with the swing rods on the motor side and the non-motor side relative to the non-flexible suspension.First published online: 22 May 2013